Analysis of maternal mortality in Jammu and Kashmir: A retrospective study based on review of field data - Saleem Ur Rehman,; Jeelani, Asif; SM Salim Khan, (Asian Journal of Medical Sciences, 2022)
Background: The inequities in provision of essential maternal healthcare have led to significant difference in maternal mortality globally. Having area specific data of maternal deaths are an important prerequisite for strengthening of reproductive and maternal health services. Aims and Objectives: The present study was conducted to estimate maternal mortality ratio (MMR) for J&K and describe the epidemiological characteristics of maternal deaths. Materials and Methods: Data regarding maternal deaths and live birth from April 2020 to March 2021 were collected. Data for maternal deaths were analyzed with respect to epidemiological parameters. MMR and lifetime risk were calculated using standard formulas. Results: A total of 91 maternal deaths were reported in the same period. It translated to an MMR of 46 for J&K. The mean age at death was 28.6 years ± 5.57. Primigravidae constituted 41.8% of deaths and most deaths (72.5%) had happened in post-natal period. Most of the deaths (78/91) had happened at tertiary level healthcare facilities with two facilities (LD Hospital, Srinagar & SMGS Hospital Jammu) reporting (52/91) of the deaths. Deaths during transit contributed to 5% of total deaths. Eclampsia and post-partum hemorrhage were the most common causes of death and contributed to around 50% of deaths. Conclusion: The maternal mortality rate was estimated to be 46 with wide inter district variations. PPH and Eclampsia were the most common causes with most deaths happening within tertiary care hospitals.